2023
DOI: 10.3390/admsci13040108
|View full text |Cite
|
Sign up to set email alerts
|

Is Customer Satisfaction Achieved Only with Good Hotel Facilities? A Moderated Mediation Model

Abstract: Modern hotel business models tend to split ownership of the property and its business operations. It can be assumed that a good-quality hotel facility per se can easily achieve high customer satisfaction. The purpose of this research was to investigate the effect of customer perception of hotel facilities on customer satisfaction by integrating the mediating effect of customer perception of the personnel and business organization and the moderating effect of the customers’ family income. Three-hundred and seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
2
4
0
Order By: Relevance
“…The findings support the evidence that income significantly impacts CS levels, with studies showing significant differences in CS among guests in hotels based on demographic factors such as income (Tefera & Migiro, 2018). Recently, Baquero (2023) suggested that high-income customers value facilities that cater to their beliefs and preferences, which enhances their satisfaction. Therefore, understanding these variations can guide businesses in developing targeted strategies to enhance satisfaction, especially for guests with lower incomes, and capitalize on the observed threshold effect.…”
Section: Discussion and Recommendationssupporting
confidence: 78%
See 1 more Smart Citation
“…The findings support the evidence that income significantly impacts CS levels, with studies showing significant differences in CS among guests in hotels based on demographic factors such as income (Tefera & Migiro, 2018). Recently, Baquero (2023) suggested that high-income customers value facilities that cater to their beliefs and preferences, which enhances their satisfaction. Therefore, understanding these variations can guide businesses in developing targeted strategies to enhance satisfaction, especially for guests with lower incomes, and capitalize on the observed threshold effect.…”
Section: Discussion and Recommendationssupporting
confidence: 78%
“…Moreover, wealthier customers tend to have more stringent views on business travel compared to leisure, likely due to higher expectations in that aspect of life (Radojevic, Stanisic, Stanic & Davidson, 2018). Baquero (2023) mentioned that high-income customers prefer facilities that cater to their beliefs and piety preferences, including exclusive food and beverage services, which enhance CS. On the other hand, Kumar and Bhatnagar (2017) indicated that there is no difference in income for CS.…”
Section: Differences In Customer Satisfaction Based On Demographic An...mentioning
confidence: 99%
“…Water parks belong to the category of amusement parks that utilize water as their core attraction (Ghorbanzade et al, 2019;Jin et al, 2015;Lee et al, 2014). Tourist attraction, accessibility, main facilities, and supporting facilities are interesting to study since these components are the basic needs of services to create satisfaction and revisit intention (Baquero, 2023;He et al, 2022;Liu et al, 2017;Mandić et al, 2018). The limitation of research so far is that it still rarely focuses on the behavior of young water park visitors, especially regarding the role of attraction, accessibility, and facilities of water park tourism.…”
Section: Literature Review Water Parks and Young Touristsmentioning
confidence: 99%
“…The provision of recreational facilities is able to increase satisfaction and revisit intention (Baquero, 2023;Markus et al, 2019;Som and Badarneh, 2011). Next, it is also believed that main facilities and supporting facilities have a positive impact on tourist satisfaction (Marzuki et al, 2017;Vengesayi et al, 2009).…”
Section: Recreational Facilities Satisfaction and Revisit Intentionmentioning
confidence: 99%
“…Firstly, one of the main limitations of our paper is that the results may not be generalizable as this study focuses on a specific geographical area with a small sample. However, given the tourist importance of this area, previous studies (e.g., see [85,86]) have focused on tourist enclaves in the Valencian Community, such as Benidorm and Alicante, although with a larger sample of hotel firms. Future research may extend the scope of analysis to other geographical areas in order to extrapolate our results.…”
Section: Discussionmentioning
confidence: 99%